Communication strategies of luxury fashion brands: Is sustainable a luxury? - González Romo, Zahaira Fabiola (2020)
The use and consumption of ecological and sustainable products imply a high cost due to the complexity of its supply chain, and luxury fashion is an industry that is increasingly influenced by the phenomenon of sustainability. "Is sustainable luxury or sustainability a luxury?" It is the main question that the current investigation seek to address through in-depth interviews with professionals in the luxury fashion sector, how do their production chains work, what strategies are used in their businesses and how do they promote ecological and sustainable values ​​through an aesthetic expression such as Haute Couture garments.